CRETACEOUS PALYNOLOGY (SPORES, POLLEN AND DINOFLAGELLATE CYSTS) OF THE SIQEIFA 1-X BOREHOLE, NORTHERN EGYPT (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Diverse and well preserved palynofloras were recognized in the Lower Cretaceous succession penetrated by well Siqeifa 1-X in northern Egypt. Dinoflagellate cysts such as Subtilisphaera senegalensis was regarded, with the spores Impardecispora apiverrucata and Aequitriradites spinulosus, as important Berriasian to Barremian species. Afropollis operculatus/zonatus pollen and spores such as Balmeisporites holodictyus, Trilobosporites laevigatus and Duplexisporites generalis are diagnostic of Aptian. The lowest occurrences of the pollen Afropollis jardinus, the spore Crybelosporites pannuceus and elaterates such as Elaterosporites klaszii, Elaterocolpites castelainii and Elateroplicites africaensis characterize the Albian/lower Cenomanian interval. The palynofloras enabled the recognition of five spore-pollen and four dinoflagellate zones, which are correlated with regional records, mainly from Egypt and Libya. The vertical distribution of terrestrial and marine palynomorphs, along with palynodebris, reflects two regressive marginal marine cycles during Berriasian-Barremian and Albian-lower Cenomanian times whereas the Aptian witnessed a transgressive open marine (inner shelf) environment. A warm humid palaeoclimate was inferred during deposition of the investigated succession of the borehole, in contrast to the known warm arid to semi-arid climate, suggested for the Northern Gondwana Realm during Early Cretaceous times. This is probably due to the palaeogeographic position of Egypt during Early Cretaceous times or, to a local reason. Palynofloras from Siqeifa 1-X borehole, with Afropollis pollen and elaterates, are of North African aspect and share the broad characteristics of the "Albian-Cenomanian Elaterates Province" of Herngreen et al. (1996). Abundance of spores and araucariacean pollen are transitional features between those in North Gondwana and Southern Laurasia but, unlikely, typical transitional assemblages lack bisaccates conifers and have Gleicheniaceae spores.
Keywords: Spores; Pollen; Dinoflagellate cysts; Age assessments; Palynology; Lower Cretaceous; Egypt